2000
DOI: 10.1067/mtc.2000.109543
|View full text |Cite
|
Sign up to set email alerts
|

Closed-chest coronary artery surgery on the beating heart with the use of a robotic system

Abstract: The introduction of robotic instrumentation has led to new minimally invasive surgical options in patients with coronary artery disease. [1][2][3][4] The application of an intrathoracic stabilizer enables closed-chest off-pump coronary artery bypass grafting (CABG) via a 4-point stab incision, avoiding sternotomy and minithoracotomy. We present a case of closed-chest off-pump CABG performed with wrist-enhanced robotic instrumentation in a patient with single-vessel coronary artery disease. The left internal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 4 publications
0
33
0
2
Order By: Relevance
“…Robotic surgery technology and techniques have made rapid advances in recent years across a wide range of clinical applications including cardiovascular surgery (Kappert et al, 2000), urology (Menon, Tewari, Baize, Guillonneau, & Vallancien, 2002), pediatrics (Gutt et al, 2002), gynecology (Falcone, Goldberg, Margossian, & Stevens, 2000), neurosurgery (Giorgi, Sala, Riva, Cossu, & Eisenberg, 2000), orthopedics (Jakopec et al, 2001), microsurgery (Siemionow, Ozer, Siemionow, & Lister, 2000), and fetal surgery (Aaronson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery technology and techniques have made rapid advances in recent years across a wide range of clinical applications including cardiovascular surgery (Kappert et al, 2000), urology (Menon, Tewari, Baize, Guillonneau, & Vallancien, 2002), pediatrics (Gutt et al, 2002), gynecology (Falcone, Goldberg, Margossian, & Stevens, 2000), neurosurgery (Giorgi, Sala, Riva, Cossu, & Eisenberg, 2000), orthopedics (Jakopec et al, 2001), microsurgery (Siemionow, Ozer, Siemionow, & Lister, 2000), and fetal surgery (Aaronson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There are some drawbacks, however, of the laparoscopic technique such as unstable video camera platform, limited motion of straight instruments, two-dimensional imaging, and poor ergonomics for the surgeon. Robotic surgery is spreading all over the world for many surgical procedures ranging from cardiac to general and urologic surgery thanks to its potential advantages overcoming the negative aspects of laparoscopic approach (Piazza et al, 1999;Reichenspurner et al, 2000;Kappert et al, 2000;Gill et al, 2000;Chen et al, 2009). The da Vinci surgical system (Intuitive Surgical Inc., Sunnyvale, CA, USA) was the first telerobotic system approved for intra-abdominal surgery in the USA by the Food and Drug Administration (FDA, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the effect of pulmonary function testing on outcomes in TECAB in 174 consecutive TECAB patients at the University of Maryland; 16 of 174 (9.2%) patients required conversion to sternotomy. h, P=0.001), and longer hospital stay (6 [3-18] vs. 5 [3][4][5][6][7][8][9][10][11] days, P=0.001).…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…No complications occurred and the patient was discharged on the 7th postoperative day. 7 Finally, in another follow-up report, Damiano et al 8 reported on 32 patients scheduled for elective primary coronary surgery who underwent endoscopic anastomosis of the LITA to the LAD. Conventional techniques were used to perform the other grafts; 31 patients underwent these procedures via median sternotomy and 1 via an anterior thoracotomy (44 patients were originally placed in the study of which 4 (9.1%) preoperatively and 8 (18.2%) intraoperatively were excluded from analysis due to "unfavorable conditions").…”
Section: History and Status Of Robotic Tecabmentioning
confidence: 99%